1999
DOI: 10.1046/j.1523-1747.1999.00513.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical Gene Delivery to Murine Skin

Abstract: We topically applied naked plasmid DNA containing the luciferase or chloramphenicol acetyltransferase cDNA directly to mouse skin. Gene expression was detected in skin samples as early as 4 h after DNA application, plateaued from 16 to 72 h post-application, and had decreased significantly by 7 d post-application. Reporter gene activity following topical DNA delivery was comparable with that produced by intradermal injection of DNA. Plasmid DNA at concentrations > or =0.25 microg per microl were required to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…[31][32][33][34] The longer duration of expression of the HoxD3 transgene in our current study is likely attributed to the methylcellulose carrier that retains DNA at the wound site and slows diffusion of the plasmid into the wound and tissue fluid. A recent study also suggested that a major limitation of plasmid DNA gene transfer was the inability of plasmid DNA to effectively enter the nucleus.…”
Section: Discussionmentioning
confidence: 79%
“…[31][32][33][34] The longer duration of expression of the HoxD3 transgene in our current study is likely attributed to the methylcellulose carrier that retains DNA at the wound site and slows diffusion of the plasmid into the wound and tissue fluid. A recent study also suggested that a major limitation of plasmid DNA gene transfer was the inability of plasmid DNA to effectively enter the nucleus.…”
Section: Discussionmentioning
confidence: 79%
“…Each of the two wounds was topically treated once daily (days 0 -5) with either empty plasmid (pEXV) or expression plasmid pEXVracV12 (constitutively active Rac1) (21). Twenty-five microliters of naked plasmid DNA (10 g) in sterile Tris-EDTA, pH 8.0, (TE) were administered onto the wound area and spread evenly using the pipette tip.…”
Section: Rac1 Gene Transfermentioning
confidence: 99%
“…Epidermal keratinocytes and dendritic cells have the ability to take up and express naked plasmid DNA upon intradermal in vivo injection and topical application, [1][2][3][4][5][6][7] making them attractive targets for gene therapy and DNA vaccination.…”
Section: Introductionmentioning
confidence: 99%